La démocratie à l’école : quels savoirs, quelles valeurs pour quelle éducation ? - Céline Chauvigné (Éducation et Socialisation)
From the example of democracy at school, we will question here the training of pupil-citizen in school. The text tries to expose, within the framework of a care of the pupils at the borders of the class, (either in school life, understood as life outside the class), the tensions between the knowledge related to the instruction (The functioning of political institutions, institutional ideals, incarnated political practices) and the social values ​​and norms that both encourage and restrict the real development of democracy. Examination of the latest institutional measures (moral and civic education, a common base of knowledge, skills and culture, etc.) highlight the difficulties of exceeding social norms in the act of educating and proposing some perspectives in order to transmit the values ​​necessary for the formation of autonomous and enlightened citizens.